2017
DOI: 10.3390/ijerph14040436
|View full text |Cite
|
Sign up to set email alerts
|

Non-Responsive Feeding Practices, Unhealthy Eating Behaviors, and Risk of Child Overweight and Obesity in Southeast Asia: A Systematic Review

Abstract: Childhood obesity is increasing dramatically in many Southeast Asian countries, and becoming a significant public health concern. This review summarizes the evidence on associations between parental feeding practices, child eating behaviors, and the risk of overweight and obesity in Southeast Asian children 2–12 years old. We systematically searched five electronic academic/research (PubMed, PsycINFO, ProQuest Nursing, Medline, and CINAHL) databases using the Preferred Reporting Items for Systematic Reviews an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
0
19
0
3
Order By: Relevance
“…Posteriormente ao uso dos filtros ou limites, foram excluídos 1.388 trabalhos e, por meio da leitura dos títulos e resumos, permaneceram 54 artigos elegíveis. Foi realizada a leitura minuciosa e integral de 14 Palfreyman et al, 2014 33 Antoniou et al, 2015 25 Remy et al, 2015 29 Russell et al, 2015 27 Ho mann et al, 2016 22 Anna Ek et al, 2016 25 Holley et al, 2016 31 Bennett et al, 2016 35 Russell et al, 2016 27 Tylka et al, 2016 15 Steinsbekk et al, 2016 16 Blaine et al, 2017 17 Melo et al, 2017 32 Crianças na faixa etária entre 3 a 6 anos de idade, uma amostra N= 439 18 Klazine et al, 2017 19 Haycraft et al, 2017 46 Lindsay et al, 2017 20 Fries et al,…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Posteriormente ao uso dos filtros ou limites, foram excluídos 1.388 trabalhos e, por meio da leitura dos títulos e resumos, permaneceram 54 artigos elegíveis. Foi realizada a leitura minuciosa e integral de 14 Palfreyman et al, 2014 33 Antoniou et al, 2015 25 Remy et al, 2015 29 Russell et al, 2015 27 Ho mann et al, 2016 22 Anna Ek et al, 2016 25 Holley et al, 2016 31 Bennett et al, 2016 35 Russell et al, 2016 27 Tylka et al, 2016 15 Steinsbekk et al, 2016 16 Blaine et al, 2017 17 Melo et al, 2017 32 Crianças na faixa etária entre 3 a 6 anos de idade, uma amostra N= 439 18 Klazine et al, 2017 19 Haycraft et al, 2017 46 Lindsay et al, 2017 20 Fries et al,…”
Section: Resultsunclassified
“…DeCosta et al, 2017 21 Powell et al, 2017 26 Jansen et al, 2017 34 Watterworth et al, 2017 22 Mães com idade ≥18 anos e crianças na faixa etária entre 4 meses e 1ano e 4meses de idade, n=330 participantes Dos 23 artigos integrantes dessa revisão, 61% apresentaram associação direta entre as práticas parentais de restrição e aumento da ingestão alimentar pelas crianças, principalmente quando o alimento estava acessível, com consequente aumento do peso [14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Trinta por cento das publicações identificaram associação significativa entre as práticas parentais de recompensa,alimentação seletiva do filho e comer na ausência de fome 18,[21][22][23][24]26 .…”
Section: Resultsunclassified
“…Preventing unhealthy feeding behaviors is highly desirable since deleterious eating habits are associated with health problems including higher risk of overweight or obesity [Lindsay et al 2017]. Because eating behavior is the result of integrated central and peripheral biological systems that are influenced by genetic, psychologic and environmental factors [MacLean et al, 2017], its optimization is highly complex and requires to fully elucidate the mechanisms that control eating behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lessard et al (2010) found that persuasion can have opposite effects depending on whether the parent is perceived to be high or low in parental warmth. In addition, a systematic review investigating the effects of non-responsive parenting practices in Southeast Asia has found that nonresponsive parenting practices are related to child overweight and obesity (Lindsay, Sitthisongkram, Greaney, Wallington, & Ruengdej, 2017). Despite this, as we shall discuss in Chapter III (Study One) later, there are very few studies that have taken into account the moderating effect of parenting styles on the effect of context-specific parenting practices.…”
Section: Parenting Style As Overall Emotional Climatementioning
confidence: 99%
“…Likewise, Ray, Kalland, et al (2013) found that restrictive guidance had stronger correlations with healthy and unhealthy food consumption when parental warmth is high. In addition, a systematic review investigating the effects of non-responsive parenting practices in Southeast Asia has found that non-responsive parenting practices are related to child overweight and obesity (Lindsay et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%